Using OpenRefine : the essential OpenRefine guide that takes you from data analysis and error fixing to linking your dataset to the Web /: the essential OpenRefine guide that takes you from data analysis and error fixing to linking your dataset to the Web. (2013) - Verborgh, Ruben; De Wilde, Max
No abstract available